RESEARCH ON STATE AND SOCIAL RELATIONSHIPS: TOPIC ON CHINESE CIVIL SOCIETY - Hu, Shi-qian (Politology, 2023)
State totalitarianism has come down in the world now, and the Chinese government has fully realized that only with teamwork of civil societies it can effectively eliminate revolts inside the society and maintain stability of the state. So the dependency of the government on civil societies is the basic reason that leads to state and society relationships change. ln the specific environments in China, how can the government achieve teamwork with civil societies while maintaining current political systern? The answer is that the government substantially supports activities of civil societies in the political system. After a brief analysis on a series reform measures introduced by the government to eliminate revolts inside the society, this paper takes some advice on its shortage. Finally this paper considers that if Chinese government could not coordinate relationships among civil societies inside and outside the system, it would face the possibility of political system shaken.